Extended Investigation of Exposure to Respirable Synthetic Amorphous Silica Dust and Its Potential Impact on Non-malignant Respiratory Morbidity - Yong, Mei; Morfeld, Peter; McCunney, Robert (Frontiers in Public Health, 2022)
Objectives: The present analysis aims to study the health impact from an occupational exposure to respirable synthetic amorphous silicas (SAS) dusts, based on the available data of the German study. Methods: The effect of cumulative exposure to respirable SAS dust on respiratory morbidity were investigated in 462 exposed male workers. A multiple exposure assessment was performed anchored by a most recent measurement series. Internal regression models in addition to Monte Carlo-Multi Model were fitted. Results: An averaged cumulative respirable SAS dust concentration of 6.44 mg/m3*years was estimated. Internal regression models suggested a reduction of 8.11 ml (95% confidence interval: 0.49 - 15.73) in forced vital capacity (FVC) per 1 mg/m3-year increase of exposure. But no effect on forced expiratory volume in one second (FEV1) and the ratio of the parameters FEV1/FVC was observed in association with exposure to respirable fraction of SAS, No adverse effects on occurrence of respiratory diseases were indicated. Conclusion: This study provides no clear evidence of adverse health effects from occupational exposure to respirable SAS.